Fire storm - Mehl, Nancy (Mehl, Nancy ; v. 2., 2019)
"When FBI profiler Kaely Quinn visits Nebraska to care for her ailing mother, she notices suspicious connections among a series of local fires and calls on her partner, Noah Hunter, to help find the arsonist. They embark on a twisted path to catch a mad man intent on Kaely's death"--